Single variable calculus - Stewart, James (Thomson Brooks/Cole, 2005)
This Student Solutions Manual, written by Jeffery A. Cole, contains detailed solutions to the odd-numbered exercises in each chapter section, review section, True-False Quiz, and Focus on Problem Solving section. Also included are solutions to all Concept Check questions. Use of the solutions manual ensures that students learn the correct steps to arrive at an answer. This solutions manual covers chapters 1-8